Turkey’s Political Role in the Middle East and Its Repercussions on the Syrian State - Matar, Ali Khidr (Journal of Economic, Administrative and Legal Sciences, 2025)
The political role of Turkey in the Middle East has undergone a radical transformation, shifting from a "zero problems" policy to a more interventionist and decisive approach. This change is driven by a strategic vision to bolster its regional influence. The study is based on the premise that this transformation is not merely a reaction to events but is part of the "Neo-Ottomanism" principles adopted by the Justice and Development Party (AKP) under the leadership of Recep Tayyip Erdoğan, capitalizing on the vacuum left by regional conflicts.The research focuses on the profound effects of Turkish intervention on the Syrian state, where it led to the fragmentation of Syrian territories by establishing direct military zones of influence, thus weakening the central government's sovereignty. It also contributed to demographic changes, as military operations resulted in population displacement and the settlement of other groups, raising serious questions about the future of Syrian unity.The study clarifies that Turkish intervention has complicated the conflict, turning Syria into an arena for competition among major regional and international powers (Turkey, Russia, Iran, and the United States), which has made finding a comprehensive political solution more difficult. The research also shows that Turkey has used economic and ideological tools to enhance its influence.In conclusion, the study affirms that Turkey's presence in Syria has become a fixed reality and a structural factor that must be considered in any future settlement. Understanding this complex role is key to comprehending the future landscape of the region.
Keywords: Turkish role; Turkish foreign policy; Middle East; Syrian crisis